Exploration of the patient's voice. (4th May 2022) - Cox, Phillip; Mihalko, Shannon L; Danhauer, Suzanne C; Kirk, Julienne K; Canzona, Mollie Rose; Black, Heather L; Shumaker, Sally A
Abstract : Diabetes self-management is a complex process in which individuals are asked to modify established health behaviors. Healthcare providers are instrumental in enhancing individual self-management and are encouraged to consider the patient perspective, often expressed indirectly. Using multidimensional analysis, this study analyzed talk to compare linguistic features used by adherent and non-adherent individuals with diabetes. In-depth telephone interviews were conducted with 108 individuals. Recruitment was stratified by sex, race and glycated hemoglobin (A1C) score. Interviewer contributions were removed from the transcripts, leaving only the participants' contributions. Using A1C score (<7%, >7%) the texts were divided into adherent and non-adherent datasets. Based on computer-assisted, quantitative analysis, ten linguistic features had a significant difference in frequency of use between the two groups. The participants in the adherent group used a greater frequency of linguistic features related to personal stance than the non-adherent group, and these expressions of personal stance were considered in relation to the participant's sense of agency. A better understanding of the way in which different subsets of individuals talk about diabetes self-management would facilitate greater healthcare provider understanding of the patient's perspective during clinical encounters to improve adherence.